Does early combination vs. Monotherapy improve clinical outcomes of clinically extremely vulnerable patients with COVID-19? Results from a retrospective propensity-weighted analysis - Maria, Mazzitelli; Maraolo, Alberto Enrico; Cozzolino, Claudia; Sasset, Lolita; Ferrari, Anna; Basso, Monica; Vania, Eleonora; Bonadiman, Nicola; Scaglione, Vincenzo; Cattelan, Anna Maria (European journal of medical research, 2024)
The potential efficacy of early combination therapy, based on an antiviral plus a monoclonal antibody, for COVID-19 in severely immunocompromised patients is matter of debate. Our aim was to describe the impact on clinical outcomes of COVID-19 treatments in severely immunocompromised individuals, evaluating differences between a combination and a monotherapy. We included severely immunocompromised outpatients with mild-to-moderate COVID-19 who received an early treatment (either monotherapy with nirmatrelvir/ritonavir or remdesivir or the combination of an antiviral plus sotrovimab). We then assessed differences between the two treatment strategies on three main outcomes (30-day mortality, access to emergency department, hospitalization), separately and as a composite by using a propensity score weighted (PSW) approach. Eighty one severely immunocompromised patients were included, 39 receiving early combination therapy and 42 receiving monotherapy. No significant difference was observed in the 30-day mortality rate and hospitalization rate between subjects in the two groups, while access to the emergency department following treatment administration was significantly higher in people who received a combination therapy. After applying the PSW, it was observed that combination therapy impacted favourably on the composite outcome, in a statistically significant fashion. In addition, PSW approach for mortality showed that age was the only significant factor influencing the death as stand-alone outcome. Early combination therapy showed a favourable impact on a composite outcome (including mortality, hospitalizations and access to emergency department) in severely immunocompromised hosts who were all vaccinated. However, further studies are needed to support our results.